Dampak Resiko Keuangan Dalam Bisnis Jasa Keuangan Perusahaan Asuransi Jiwa di Era Pandemi Corona - Dodi Siswanto (Program Studi Manajemen, Universitas Al Ghifari, 2021)
Future uncertainty that can occur in financial services companies is a risk that must be faced and must receive serious attention. business financial services companies are based on the principle of trust, in the financial business the factor of ensuring liquidity is very crucial because it is a benchmark for the sustainability of the company. The writing of this article is to examine the impact of financial risks from insurance service companies, through a literacy approach sourced from journals, laws and regulations, and theories from experts as well as issues related to insurance service companies in Indonesia. The investment decision of the company can have a significant impact on the company's liquidity. The company must be able to place the funds obtained from the insured's premium payment in a potential sector so that the problem of default in the future can be avoided. The problems in an insurance company can be seen from the gap between assets and liabilities (there are more claims than assets), this condition causes the company to become ilikud. Companies are not careful when placing their funds in investing can determine the condition of the company's liquidity in the future. the role of managers in determining financial strategies in investing must be very mature taking into account the possible financial risks. The risk impact of financial decisions must be taken seriously by management so that the risk of future losses can be minimized.Keywords: Risk, Finance, Service Company, Insurance